Functional adaptation underpinned the evolutionary assembly of the earliest vertebrate skeleton. Issue 6 (1st October 2014) - Murdock, Duncan J. E.; Rayfield, Emily J.; Donoghue, Philip C. J.
SUMMARY Conodonts are the first vertebrates to bear a mineralized skeleton, restricted to an array of tooth‐like feeding elements. The functional implications for the development of tooth‐like elements differentiated into two tissues is tested using 2D finite element modeling, mapping the patterns of stress and strain that elements with differing material properties exhibited during function. Addition of a stiff crown does not change the patterns of stress, rather it reduces the deformation of the element under the same force regime, and distributes stress more evenly across the element. The euconodont crown, like vertebrate dental enamel, serves to stiffen the element and protect the underlying dentine. Stiffness of the crown may be a contributing factor to the subsequent diversity of euconodont form, and logically function, by allowing a greater range of feeding strategies to be employed. The euconodont crown also serves as an analogue to enamel and enameloid, demonstrating that enamel‐like tissues have evolved multiple times in independent vertebrate lineages, likely as a response to similar selective pressures. Conodonts can, therefore, serve as an independent test on hypotheses of the effect of ecology on the development of the vertebrate skeleton.